Cultural Diversity and Classroom Experience: A Phenomenological Case of Graduate Students’ Response to New Classroom Experience - Oscar S. Mmbali; L. A. Pavithra Madhuwanthi (International Journal of Management, Knowledge and Learning, 2015)
In this study we analyse students’ lived experiences in a cross-cultural classroom context, with the aim of understanding: (1) What is the impact of a culturally diverse classroom experience on graduate school students’ learning? (2) Which larger ramifications, if any, exist from this experience? The participants were PhD and Masters Students in a university in Thailand. This was a phenomenological study. Themes emerging from complex cultural practices of international students, professors and Thai students inform, hinder and promote learning. Findings from this study can inform pedagogy particularly at graduate school level, where cultural diversity matters in classroom experience.